The structure of a one-electron oxidized Mn(iii)-bis(phenolate)dipyrrin radical complex and oxidation catalysis control via ligand-centered redox activity. Issue 41 (22nd September 2016) - Lecarme, Laureline; Chiang, Linus; Moutet, Jules; Leconte, Nicolas; Philouze, Christian; Jarjayes, Olivier; Storr, Tim; Thomas, Fabrice
Abstract : One electron-oxidation produces a structurally characterized Mn(iii ) radical complex, which catalyzes the isomerization of epoxides in addition to the epoxidation of olefins in the presence of PhIO. Abstract : The tetradentate liganddppH3, which features a half-porphyrin and two electron-rich phenol moieties, was prepared and chelated to manganese. The mononuclear Mn(iii )-dipyrrophenolate complex1 was structurally characterized. The metal ion lies in a square pyramidal environment, the apical position being occupied by a methanol molecule. Complex1 displays two reversible oxidation waves at 0.00 V and 0.47 V vs . Fc + /Fc, which are assigned to ligand-centered processes. The one-electron oxidized species1 + SbF6 − was crystallized, showing an octahedral Mn(iii ) center with two water molecules coordinated at both apical positions. The bond distance analysis and DFT calculations disclose that the radical is delocalized over the whole aromatic framework. Complex1 + SbF6 − exhibits an S tot = 3/2 spin state due to the antiferromagnetic coupling between Mn(iii ) and the ligand radical. The zero field splitting parameters are D = 1.6 cm −1, E / D = 0.18(1), g ⊥ = 1.99 and g ∥ = 1.98. The dication1 2+ is an integer spin system, which is assigned to a doubly oxidized ligand coordinated to a Mn(iii ) metal center. Both1 and1 + SbF6 − catalyze styrene oxidation in the presence of PhIO, but the nature of the main reaction product is different. Styrene oxide is the main reaction product when using1, but phenylacetaldehyde is formed predominantly when using1 + SbF6 − . We examined the ability of complex1 + SbF6 − to catalyze the isomerization of styrene oxide and found that it is an efficient catalyst for the anti-Markovnikov opening of styrene oxide. The formation of phenylacetaldehyde from styrene therefore proceeds in a tandem E–I (epoxidation–isomerization) mechanism in the case of1 + SbF6 − . This is the first evidence of control of the reactivity for styrene oxidation by changing the oxidation state of a catalyst based on a redox-active ligand.